Nazywam sie Czerwien - Pamuk, Orhan, 1952-; Chmielowska, Danuta (Kraków : Wydawn. Literackie, 2007)
A furor erupts in sixteenth-century Istanbul when the Sultan commissions the European-style illumination of a great book, and the situation worsens when one of the miniaturists vanishes mysteriously.
Keywords: Illumination of books and manuscripts -- Fiction; Islam and art -- Fiction; Istanbul (Turkey) -- Fiction